Thermal performance evaluation of double panel glass windows - Salleh, Naziah Muhamad; Azmi, Muhamad Haziq; Salim, Nuzaihan Aras Agus; Kamaruzzaman, Syahrul Nizam; Azizi, Nurul Sakina Mokhtar (Construction Research Institute of Malaysia, 2018)
Technology of glass used in double glazing window for thermal insulation is known as Low Emissivity Glass (Low E). It has a transparent metallic coating that works into the heating energy. The U-value of a double glazing window in this experiment is the calculated by using software programs developed at Lawrence Berkeley National Laboratory (LBNL) called WINDOW 7.3. This software can determine which the double glazing windows Low E Glass or Clear Glass and with the lowest U-value are the most efficient and show in result. The goal of this research was to assess the thermal surface performance and daylight penetration of Double Panel Window (DPW) with difference type of glass. The U-Value, thermal transmittance and relative solar heat gain coefficient values obtained from both experiments with computer simulations. This can lead to a reduction of about 50-70% direct solar heat and still maintain high visibility by using low emissivity glass.